AB0952 COMPARISON OF THE EFFECT BETWEEN BISPHOSPHONATE AND DENOSUMAB ON BONE MINERAL DENSITY AND RADIOGRAPHIC PROGRESSION IN PATIENTS WITH ANKYLOSING SPONDYLITIS: A PILOT STUDY - Kim, M.Y.; Kang, K.Y.; Hong, Y.S. (Annals of the rheumatic diseases, 2023)
Osteoporosis is a frequent complication of ankylosing spondylitis (AS). Althogh there are no clear guidelines for the treatment of this secondary osteoporosis in AS, antiosteoporotic agents including bisphosphonate were used according to the same guidelines for primary osteoporosis. Also, approved by European Medicines Agency (EMA) in 2010, denosumab is being widely used. To compare the effect between bisphosphonate and denosumab on bone mineral density and radiographic progression in patients with AS for one year. Among twenty-four patients with AS, sixteen patients were treated with bisphosphonate and nine patients with denosumab. BMD in the lumbar spine and right femur was measured by dual energy x-ray absorptiometry (DEXA) at baseline and one year after treatment. Radiographic progression was scored using the modified Stoke AS Spinal Score (mSASSS). Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), and bone markers (bone-specific alkaline phosphatase (ALP), Collagen type 1 cross-linked C-telopeptide) were used to assess disease activity. Mean BMD values in the lumbar spine and total hip at one year increased when compared to those at baseline in both the bisphosphnate and denosumab groups (P=0.006 and 0.007 in bisphosphonate group, 0.015 and 0.036 in denosumab group). The increment was greater in denosumab group. The mean BMD in L-spine and total hip increased by 11.0% and 4.9% in denosumab group, while 9.0% and 2.7% in bisphosphonate group. There were no differences in disease activities such as BASDAI, ASDAS-CRP, ESR, and CRP between two groups. mSASSS and number of syndesmophyte also revealed no significant differences, suggesting that denosumab does not adversely affect disease activity and radiographic scores compared to bisphosphonate. Both bisphosphonate and denosumab increase L-spine and total hip BMD, while not affecting disease activity and spinal new bone formation. Further prospective studies with larger subject numbers are needed. [1]Bone. 2009 May;44(5):772-6. [2]Br J Clin Pharmacol. 2021 Feb;87(2):644-651. NIL. None Declared. Table 1Comparisons of the changes of clinical measure and radiographic scores between bisphophonate and denosumabChange from baseline to year oneBisphosphonate (n=15)Denosumab (n=9)P-valueBASDAI1.5 ± 2.42.9 ± 2.80.215ASDAS-CRP0.9± 1.21.7 ± 1.30.174ESR, mm/h17.2 ± 24.831.0 ± 35.90.519CRP, mg/l13.7 ± 31.524.5 ± 44.00.446Bone-specific ALP, μg/l-0.7 ± 14.64.2 ± 4.30.379C-telopeptide, ng/ml-0.7 ± 2.70.128 ± 0.10.411mSASSS in C- and L-spine0.7 ± 0.90.4 ± 1.40.411Number of syndesmophytes in C- and L-spinea0.1 ± 0.30.2 ± 0.40.558Changes are calculated as base value subtracted from one year value. BASDAI: Bath Ankylosing Spondylitis Disease Activity Index. ASDAS: Ankylosing Spondylitis Disease Activity Score. ALP: ankaline phosphatase. mSASSS: modified SASSS. C-: cervical. L-: lumbar.